De Novo Migraine With Aura After Surgical Repair of Aortic Coarctation. Issue 5 (2nd December 2016) - Kato, Yuji; Hayashi, Takeshi; Kobayashi, Toshiki; Masuoka, Ayumu; Abe, Tetsuya; Hasebe, Takahiro; Tanahashi, Norio; Takao, Masaki
Abstract : Coarctation of the aorta (CoA) is reported to be associated with an increased risk for migraine. We describe here the case of a 13‐year‐old female patient who presented migraine with aura after surgical repair of CoA with a stent. As possible reasons for her condition, we postulate host responses to stent placement and/or disturbed cerebral autoregulation related to intracranial hypertension before the surgical repair and hypotension afterward, leading to hypoperfusion. This case demonstrates that de novo migraine with aura can occur after surgical repair of CoA and should be recognized as a potential complication.